Fatal Asian Giant Hornet‟s Sting: First Case Series from Kumaon Hills of Uttarakhand, India - Singh, Paramjeet; Kumar, Ashok; Saxena, Sandeep Raj; Singh, Yatendra; Rawat, Vinita; Bhaisora , C P (Journal of Indian Academy of Forensic Medicine, 2015)
Hornet stings are medically important stings which can cause allergic manifestations and in severe cases, may lead to acute renal failure (ARF), myocarditis and hepatitis. Venom from hornet stings can also contribute to myocardial injury or liver impairment. The delay in diagnosis, treatment and unawareness of fatal complication may also be a contributory factor for fatal outcome. In the remote, backward area of hills of Uttarakhand, where the emergency medical facilities are not easily available, lead to increase mortality. Here, we report the case series of farmers who were working in their field in a village at an altitude of around 6500 feet above sea level. Out of six farmers who were bitten by hornet three died before reaching our hospital and one in our hospital. Only two farmers could survive out of six. We are describing three cases of hornet stings that reached our hospital leading to ARF, myocarditis and hepatitis. Case two complicated with ARF and myocarditis and case three with hepatitis. Both of these recovered their body physiology after a 26 days and 6 day stay in the hospital, respectively, whereas Case one died.